1989
DOI: 10.1149/1.2096944
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Evaluation of Wet and Dry Cleaning Procedures for Silicon Device Fabrication

Abstract: Three different cleaning procedures of silicon wafers are investigated: (i) standard wet clean, (ii) combination of UV/ oxygen and wet cleans, and (iii) entirely dry clean consisting of UV/oxygen, and thermally enhanced remote microwave ABSTRACT Using point contact Josephson junctions fabricated by Y-Ba-Cu-O high-Tc superconductors, Shapiro steps (ac Josephson effect) were observed. It was found that condensed pair electrons exist in high-Tc ceramics. AC Josephson effect was observed at 77 K when the device wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Improvements in oxide qualities have been attained by applying the technique after SC-1/ SC-2/HF-H20, immediately before oxidation (62). Ruzyllo et al (1989) have shown that UV-O2 cleaning can replace SC-1 for removing organics (63), and Kaos reported improvements in properties of thermal oxide films (60). Hoenig (1988) investigated the use of dry ice snow for removing particles from wafers (64).…”
Section: Alternative Cleaning Techniquesmentioning
confidence: 99%
“…Improvements in oxide qualities have been attained by applying the technique after SC-1/ SC-2/HF-H20, immediately before oxidation (62). Ruzyllo et al (1989) have shown that UV-O2 cleaning can replace SC-1 for removing organics (63), and Kaos reported improvements in properties of thermal oxide films (60). Hoenig (1988) investigated the use of dry ice snow for removing particles from wafers (64).…”
Section: Alternative Cleaning Techniquesmentioning
confidence: 99%
“…[1][2][3] Surface cleaning prior to epitaxy is particularly important, as improper removal of surface oxides and organic contaminants has been shown in Si homoepitaxy to result in an increase in the density of stacking faults and dislocations from <10 4 /cm 2 to >10 10 /cm 2 4-15 and a concomitant decrease in device performance and yield. [16][17][18][19][20][21][22] Studies of the heteroepitaxial growth of Si x Ge 1Ϫx alloys on Si have also shown that residual oxide and organic contaminants act as the preferred sites for nucleation of misfit dislocations. 15 The control of defects is of paramount importance in epitaxial films of SiC, as a range of structural and electrical defects are currently limiting the application of this material for several types of high power, and high temperature electronic devices and for substrates for III-N nitride heteroepitaxy.…”
mentioning
confidence: 99%
“…A UV-ozone treatment is a dry cleaning technique typically used to remove organic contamination from the Si surface. [4][5][6] This technique leaves the Si surface passivated with a "dry" oxide (ϳ1 nm thick). In both cases, the presence of the oxide may detrimentally effect next step processing.…”
mentioning
confidence: 99%